Calcium Treatment Alleviates Pericarp Browning of ‘Nanguo’ Pears by Regulating the GABA Shunt After Cold Storage - Li, Jiaxin; Zhou, Qian; Zhou, Xin; Wei, Baodong; Zhao, Yingbo; Ji, Shujuan (Frontiers in Plant Science, 2020)
Long-term storage of pear fruit at low temperature can retard senescence but may result in pericarp browning. We previously reported that increasing endogenous γ-aminobutyrate (GABA) content by exogenous GABA treatment can maintain mitochondrial structure integrity, thereby alleviating pericarp browning of ‘Nanguo’ pears after cold storage. Here, we tested the effectiveness of Ca2+ treatment on pericarp browning in relation to GABA biosynthesis. Fruit browning was reduced by treatment with Ca2+ after 180 d of storage. Pericarp Ca2+ and calmodulin content in treated fruit increased, and concomitantly, endogenous GABA content, key GABA synthesis-related enzyme activity, and gene expression were upregulated. Moreover, the mitochondrial structure in the pericarp tissue was found to be well preserved. Thus, Ca2+ treatment effectively reduced pericarp browning of refrigerated ‘Nanguo’ pears owing to improvement in the GABA biosynthesis capacity in the fruit.